Absolute Configuration of the Phenylpropanoid Isolated from Peperomia tetraphylla. Issue 10 (2nd October 2013) - Yu, Yanchao; Lu, Xiaowei; Wu, Wenju; Wu, Yikang; Liu, Bo
Abstract A recently identified phenylpropanoid isolated from Peperomia tetraphylla was synthesized in enantiopure forms using an aldol condensation of enantiopure (R)‐N‐acetyl 4‐phenyl‐oxazolidin‐2‐one as the key step. With the aid of the single crystal X‐ray crystallographic analysis of the synthetic sample, the configuration for the natural product was unambiguously established. Corrected/updated 13C NMR and optical rotation are also presented.